2017
DOI: 10.1074/jbc.m116.761585
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Domains Required for Fibroblast Growth Factor 1 and 2 Signaling through Fibroblast Growth Factor Receptor 1c

Abstract: A small library of well defined heparan sulfate (HS) polysaccharides was chemoenzymatically synthesized and used for a detailed structure-activity study of fibroblast growth factor (FGF) 1 and FGF2 signaling through FGF receptor (FGFR) 1c. The HS polysaccharide tested contained both undersulfated (NA) domains and highly sulfated (NS) domains as well as very well defined non-reducing termini. This study examines differences in the HS selectivity of the positive canyons of the FGF1 2 -FGFR1c 2 and FGF2 2 -FGFR1c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 71 publications
(91 reference statements)
0
34
0
Order By: Relevance
“…These features are thought to represent the basis for the ability of HS chains to strongly and specifically interact with proteins (23,25,48). Some proteins such as fibroblast growth factor 2 (FGF2) and antithrombin require specific modifications of HS for optimal binding including 3-O sulfation (49)(50)(51), whereas other proteins such as IL-8 and thrombin mainly rely on HS domain structure or charge density, respectively (52,53). At present, relatively little is known about HS structural features mediating BMP interactions and whether different BMPs require distinct HS modifications and segments for optimal binding (48,54), though the BMP antagonist Noggin preferentially binds to HS carrying N-, 6-O-and 2-O-sulfates (55).…”
Section: Discussionmentioning
confidence: 99%
“…These features are thought to represent the basis for the ability of HS chains to strongly and specifically interact with proteins (23,25,48). Some proteins such as fibroblast growth factor 2 (FGF2) and antithrombin require specific modifications of HS for optimal binding including 3-O sulfation (49)(50)(51), whereas other proteins such as IL-8 and thrombin mainly rely on HS domain structure or charge density, respectively (52,53). At present, relatively little is known about HS structural features mediating BMP interactions and whether different BMPs require distinct HS modifications and segments for optimal binding (48,54), though the BMP antagonist Noggin preferentially binds to HS carrying N-, 6-O-and 2-O-sulfates (55).…”
Section: Discussionmentioning
confidence: 99%
“…HBP include growth factors, cytokines, and most, if not all, proteins able to form amyloids, such as the Aβ peptide, tau, α‐synuclein, huntingtin, superoxide dismutase, prion protein, etc. It has largely been reported that by interacting with growth factors and cytokines at the cell surface, HS participate to modulation of cell signaling , and that in the ECM, HS protect HBP proteins from proteolytic degradation, increasing their bioavailability . By analogy, HS can interact with amyloidogenic proteins, increasing their bioavailability, but also by prompting their aggregation.…”
Section: Heparan Sulfatesmentioning
confidence: 99%
“…However, the specific mechanisms by which these species are generated in vivo and how they exert their toxic effects are not yet fully understood. Numerous studies suggest that HS participate to the different phases of amyloids formation, or that they are involved in alternative fibril growth pathways proposed to compete in the different stages of the protein aggregation process .…”
Section: Protein Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…While FGF1, the prototypic member of the FGF family, is able to bind and activate all of the FGF receptor variants, FGF2 is unable to activate FGFR2 IIIb and FGFR3 IIIb, accounting at least in part for the differences in action of these two growth factors under certain contexts [12]. When FGF2 comes into contact with its receptor, an interaction mediated by heparin sulfate proteoglycans on the cell surface [13–15], it induces structural changes in FGFR dimers leading to increased intracellular receptor tyrosine kinase activity [16]. Intracellular adaptor and effector proteins are recruited to transduce the growth factor signal, leading to stimulation of myriad pathways, most notably the mitogen-activated protein kinases (MAPKs) [1720], but also other pathways such as Akt/mTOR [2123], STAT [2426], and PLCγ [2730] (Figure 2).…”
Section: Fgf2 Signalingmentioning
confidence: 99%